Pre-Design user-centred investigation of a serious game for mental health literacy: a study of Malaysian youth - Abdul Aziz, Nurul Ulfa; Ibrahim, Roslina; Abdullah, Firdaus (Universiti Teknologi MARA, Perak, 2025)
Mental health (MH) conditions are projected to become the leading cause of global disease burden by 2030, which indicates a need to improve mental health literacy (MHL), especially among youth. Digital gaming is rapidly gaining popularity in Malaysia, with serious games (SGs) increasingly recognition as promising tools for education, engagement, and behavioural change. However, low engagement and poor retention in digital MH interventions persist, often due to insufficient user-centred design and a limited understanding of user preferences. Therefore, this study presents a preliminary, user-centred investigation of Malaysian youths' attitudes, needs, and motivations regarding SGs for MHL. A cross-sectional survey was conducted with 419 respondents aged 18–25. The data were analysed using SPSS, employing ANOVA, t-test, and correlation analyses. Research findings were interpreted through the Mechanics–Dynamics–Aesthetics framework to inform game design. Results show high baseline MHL (M = 4.19/5) and generally positive attitudes toward SG-based learning (M = 3.81–4.08). Significant correlations were found between openness to SGs and key MHL components namely self-help strategies (r = 0.421), help-seeking behaviour (r = 0.381), and MH knowledge (r = 0.395). These findings suggest that well-designed games hold promise for supporting proactive MH engagement. A weaker correlation regarding erroneous beliefs (r = 0.253) points to a need for more targeted anti-stigma content. Nearly 25% of respondents preferred puzzle-based games, primarily motivated by the need for emotional relief and creative expression.